ՄԱԿ–ի մասնակցությունը Իրաքում օրինաստեղծ գործընթացներին 2005 թվականին - Սամվելյան, Կարինե («Զանգակ - 97»)
The aiticle deals with the analyses of the law-building process in Iraq during the 2005 year: the direct elections of the Transitional National Assembly on 30 Januaiy 2005, the drafting of a new Constitution for Iraq and the recent approval of the draft Constitution by the people of Iraq on 15 October 2005, the election by 15 December 2005 of a government pursuant to a newly adopted Constitution.
Keywords: Պատմություն; Քաղաքականություն; Իրաք